2008
DOI: 10.1126/science.1153625
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Optical Analog of the Event Horizon

Abstract: The physics at the event horizon resembles the behavior of waves in moving media. Horizons are formed where the local speed of the medium exceeds the wave velocity. We use ultrashort pulses in microstructured optical fibers to demonstrate the formation of an artificial event horizon in optics. We observed a classical optical effect, the blue-shifting of light at a white-hole horizon. We also show by theoretical calculations that such a system is capable of probing the quantum effects of horizons, in particular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
792
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 717 publications
(807 citation statements)
references
References 27 publications
14
792
1
Order By: Relevance
“…Interesting proposals have been done also in the optical domain when Leonhardt and Piwnicki proposed to create an optical black hole [10]. The idea is feasible since the propagation of light in a moving medium resembles many features of a curved spacetime and very recently ultrashort pulses in optical fibers demonstrated the formation of an artificial event horizon [11].…”
Section: Introductionmentioning
confidence: 99%
“…Interesting proposals have been done also in the optical domain when Leonhardt and Piwnicki proposed to create an optical black hole [10]. The idea is feasible since the propagation of light in a moving medium resembles many features of a curved spacetime and very recently ultrashort pulses in optical fibers demonstrated the formation of an artificial event horizon [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the flowing fluid, the wavenumber of the escaping 'blueshifted' zero-wavenumber incoming wave is the solution to the equation vk Z ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi gk tanhðkhÞ p , where v is the local velocity of the fluid. See also the paper in this issue by and Philbin et al (2008) where the equivalent phenomenon is demonstrated for a white hole horizon formed in an optical fibre due the nonlinearities in the refractive index of the fibre caused by an intense pulse of light in the fibre. Again, a lower frequency wave incident on the white hole horizon is blue shifted until the group velocity of the wave is less than the velocity of the pulse.…”
Section: Methodsmentioning
confidence: 99%
“…In 2008, Philbin et al [13] demonstrated the feasibility of creating artificial event horizons with a moving refractive-index front (RIF) in dispersive optical media. They estimated a temperature of 1000 K and ushered in the field of optical analogs [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%